Journal Amy Zoe Mason - Atkinson, Kristine; Atkinson, Joyce (New York Simon & Schuster, 2006)
A series of clues and revelations documenting an artist's mysterious fate, presented in collage-style newspaper clippings, e-mails, and private writings, invites readers to search its pages for visual and verbal clues.
"The short live and mysterious death of Amy Zoe Mason"--Cover.
Keywords: Mason, Amy Zoe (Fictitious character) -- Fiction; Mystery fiction